EVOLUTION OF CHROMOSOMAL ABERRATIONS AND TELOMERES AFTER A SINGLE SCAN IN NON-CANCER PATIENTS - Akiana, Francis; MEDENOU, DATON (My University, 2023)
Recent epidemiological investigations demonstrate an increased risk of cancer in children and adolescents following exposure to low-dose ionizing radiation from diagnostic were computed tomography scans with a cumulative dose of approximately 50 mSv. Peripheral blood lymphocytes from 50 non-cancer patients before and 24 hours after a CT scan were obtained. Chromosomal and telomeric aberrations were performed after staining by fluorescence hybridization of telomeres and centromeres. The frequency of these aberrations was compared to the calculated effective radiation dose using a computational dosimetry system and a dose-length product in a scanner. A significant increase in DSB resulting from all chromosomal aberrations after CT exposure was observed. A significant increase in telomere aberrations was observed after CT exposure. However, no correlation was observed between the effective radiation dose and the frequency of chromosomal and telomeric aberrations. It should be noted that the increase in chromosomal and telomeric aberrations was age-dependent. We were demonstrated in this study for the first time the significant increase in telomere aberrations after CT exposure. This loss of telomere functionality is played a major role in the continuation of chromosomal instability. These results could be used in the monitoring of populations exposed to low doses.
Keywords: Scanner; Dicentric; DSB; Dose-length product; Age; Low-dose.